Characterisation and leitmotif: archetypal imageries in Malaysian festival Tv advertisements - Jamaluddin Aziz,; Arina Anis Azlan,; Abdul Latiff Ahmad, (Faculty of Social Sciences & Humanities, UKM., 2011)
This paper seeks to analyse archetypal imageries in some TV advertisements that are produced in conjunction with religious festivals and the Independence Day celebrations in Malaysia.Adopting literary archetypes as key concepts, the advertisement texts are textually analysed, focussing on the recurrent leitmotivs as well as characterisations in order to establish the presence of archetypal imageries. Jungian’s theorisation of the archetype is used as the main analytical perspective. We argue that as archetypal imageries function as a synecdoche for something more universal,it therefore is one of the most important reasons why these advertisements appeal to the mass audience. In addition, since cultural nuances inform the characterization and leitmotif of the archetypes, we opine, that they are able to expose contemporary anxiety.